EJ12 girl hero: drama queen - MCFARLANE, SUSANNAH; SUSANNAH MCFARLANE (New York Scholastic, 2011)
follows Emma Jacks, a 10-year-old spy for the SHINE agency who balances normal school anxieties$1 (Blike friend drama$1 (Bwith high-stakes missions.s
Keywords: "Shining Star" agent for the agency SHINE, at school she is a normal girl struggling with friendship issues, mean girls, and daily anxieties; She needs to infiltrate the movie set and stop SHADOW before it's too late